Acquired non-hypertrophic and non-peptic primary pyloric functional obstruction (Jodhpur disease) first time described in African children - Tresphory, Boniphace; Calisti, Alessandro (International Surgery Journal, 2025)
The occurrence of Jodhpur Disease (JD) in two African children is reported. It is a rare, acquired, primary gastric outlet obstruction typical of Asian patients, mainly from India, not related to anatomic lesions, muscular hypertrophy, or peptic ulcer of the pylorus. It typically presents at a mean age of 2.9 years, predominantly in males. Two males, 2 and 12 years old, presented with non-bilious vomiting in the last three weeks and two months, with electrolyte imbalance and malnutrition. Helicobacter pylori infection was excluded. Ultrasound, Gastrointestinal Radiology and Gastroscopy concurred to identify the features of JD. Pyloroplasty reestablished regular transit. First described in 1997, JD appears to be confined to the Asian context. Its etiology is undefined. Occurrence in previously healthy children has been attributed to a possible neuromuscular enzymatic functional pathology. Nutritional, environmental or genetic causes have been speculated. JD disease responds to a simple pyloroplasty, followed by patient recovery. JD in two African children denies the assumption that it is exclusive to Asian individuals. It should be considered in other contexts, particularly in the presence of persistent, unexplained vomiting and malnutrition. If recognized with adequate expertise, it can be resolved with a simple procedure.